ETHNOSOCIAL CONSEQUENCES OF DEPOPULATION OF MOUNTAIN TERRITORIES: DAGESTAN AND NORTH OSSETIA - Magomedhanov, Magomedhan Magomedovic; Sadovoj, Aleksandr Nikolaevic (History, Archeology and Ethnography of the Caucasus, 2021)
Unlike the transboundary regions of Mountain ecosystems in Europe (Alps) with high population density and the integration of the rural economy into the regional and World markets, most of the Mountainous regions of the Russian Federation are characterized by the stability of traditional forms of nature management and life support, which determine, on the one hand, natural (or "old") distinctiveness of the economy of rural enclaves and, on the other hand, the preservation of social institutions based on family and relative ties, the solidarity of fellow villagers, on the cohesion of the rural community and the viability of traditional culture and ethnic identification. Regarding the general trends and consequences of the migration of inhabitants of Mountainous regions of Dagestan and North Ossetia to the lowland, it can be concluded that the prospects of ethnocultural dynamics in these republics are determined not only by the factors of urbanization, the growth of the absolute number and proportion of the population of predominantly Russian-speaking lowland urban and rural settlements and by the functional stagnation of local languages, but also by the demographic depression, depopulation of Mountainous territories, the gradual disappearance of Mountain villages, which can be considered almost the only mono-ethnic enclaves and social environments that ensure the reproduction of ethnolinguistic and ethnocultural identity in generations. In this regard, the importance of regional and federal social policy courses aimed at sustainable socio-economic and environmental development of Mountainous territories, preserving their demographic potential and ethnocultural particularities is emphasized.